RANCANG BANGUN DASHBOARD UNTUK VISUALISASI KINERJA PENJUALAN PRODUK (STUDI KASUS DRAGONWONG.COM) - Wisudawanto, Munir Agung; Setiawan, Henry Bambang; Jatmika, Kurniawan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Dragonwong.com is one of many website online store that sells the card game 'Yugi-Oh'. System users have difficulties in monitoring and controlling the performance of sales on the website in order to achieve the sales target. The existing system has not been able to provide visualization information of product sales performance that are going on along with the changes that occur in real time to provide awareness of the things that need to be responded quickly.Based on description above, then built product sales performance dashboard for dragonwong.com. Product sales performance dashboard is categorized into three according to the business activities are supported (strategic, tactical, and operational).Once the system is completed designed, built, and tested, product sales performance dashboards can display a visualization information about the condition of product sales performance. Visualization of the information can be used as Â materials to monitor and control the sales performance of products on the site dragonwong.com.